Determination of Consumer Credit Demand at Regional Development Banks: A Case Study of PT Bank Sulselbar - Anniza Reskywana Dwi Putri; Diah Retno Dwi Hastuti; Sri Astuty; Irwandi Irwandi; Muhammad Imam Ma’ruf (Jurnal Ilmu Ekonomi JIE, 2026)
This study analyses the effects of prime lending rates, the number of consumer credit accounts, and inflation on consumer credit distribution at PT Bank Sulselbar for the 2020–2024 period using a quantitative approach based on secondary data from PT Bank Sulselbar's financial statements and the Central Statistics Agency. The analysis was conducted using multiple linear regression supported by the classical assumption test. The results show that interest rates and the number of accounts have a positive and significant effect on consumer credit distribution, while inflation has a negative and significant effect. Simultaneously, all three variables have a significant effect, with an Adjusted R² of 0.904, indicating the model's ability to explain variation in consumer credit. These findings confirm that PT Bank Sulselbar's consumer credit distribution is more influenced by internal banking factors and the expansion of financial inclusion than inflation, thus managing competitive interest rates and increasing access to financial services are important strategies in supporting intermediation performance and regional economic growth